Manifestations of the Narrator in the Poetry Collection abariq Mahashama by Abdul WahabAl-Bayati (مجلة إحالات, 2026)
This study explores the presence of the "narrator" in its various forms in the collection "ShatteredPitchers" by the Iraqi poet Abdul Wahhab Al-Bayati, revealing the aesthetics of the narrative details employed by the poet in this collection. The research begins with the climax hypothesis that AlBayatiThe research explores the manifestations of the narrator: tracing the ideas that focus on thenarrator's voice in the collection's poems, whether as an omniscient narrator, a participant in theevents, or hidden behind the pronouns of the speaker, the addressee, or the narrator. In addition tothe distance separating the narrator from the events and characters, this is found in the types ofnarration and the perspective.and other effects that lend the poetic text a pictorial character and also contribute to shapingits aesthetics. We will explore the multiplicity of narrators among the authors and among thevarious poems in the collection, and how this diversity contributes to influencing the horizons ofinterpretation. We will explore the artistic and aesthetic implications of this diversity of narrativevoices, and how Al-Bayati was able to skillfully employ the techniques of correspondence in aunique and distinct poetic experience in his collection "Shattered Pitchers," which subsequentlyhelped us understand this pioneering poetic work.